2005
DOI: 10.1094/mpmi-18-1296
|View full text |Cite
|
Sign up to set email alerts
|

Pyramiding Unmarked Deletions in Ralstonia solanacearum Shows That Secreted Proteins in Addition to Plant Cell-Wall-Degrading Enzymes Contribute to Virulence

Abstract: Ralstonia solanacearum, like many phytopathogenic bacteria, makes multiple extracellular plant cell-wall-degrading enzymes (CWDE), some of which contribute to its ability to cause wilt disease. CWDE and many other proteins are secreted to the milieu via the highly conserved type II protein secretion system (T2SS). R. solanacearum with a defective T2SS is weakly virulent, but it is not known whether this is due to absence of all the CWDE or the loss of other secreted proteins that contribute to disease. These a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
99
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(107 citation statements)
references
References 40 publications
2
99
0
2
Order By: Relevance
“…Finally, the crystal-violet-bound biofilm was dissolved in 1 % SDS and quantified by measuring OD 570 . Swimming motility assay was performed as described previously (Liu et al, 2005). Because of the variable swimming activity of R. solanacearum wild-type strains (our unpublished data), swimming motility of strains in Pss4 background was assayed in 0.3 % agar medium, while that in Pss190 background was tested in 0.22 % agar medium.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the crystal-violet-bound biofilm was dissolved in 1 % SDS and quantified by measuring OD 570 . Swimming motility assay was performed as described previously (Liu et al, 2005). Because of the variable swimming activity of R. solanacearum wild-type strains (our unpublished data), swimming motility of strains in Pss4 background was assayed in 0.3 % agar medium, while that in Pss190 background was tested in 0.22 % agar medium.…”
Section: Methodsmentioning
confidence: 99%
“…The bacteria reportedly produce one b-1,4-endoglucanase (Egl), one endopolygalacturonase (PehA), two exopolygalacuturonases (PehB and PehC), one b-1,4-cellobiohydrolase (CbhA) and a pectin methyl esterase (Pme). Genetic inactivation of single genes has shown that Egl, PehA and PehB each contribute to its virulence (Liu et al 2005). Furthermore, Liu et al showed that a mutant lacking the six genes encoding these six CWDEs wilted plants significantly more slowly that the wildtype.…”
mentioning
confidence: 99%
“…Moreover, an attempt to demonstrate phytopathogenicity of B. thailandensis on Oryza sativa (rice) plants was similarly unsuccessful (34). These results, coupled with observation that, unlike those of R. solanacearum and Xanthomonas spp., the genomes of B. thailandensis and B. pseudomallei encode no plant cell wall-degrading enzymes (e.g., pectate lyases, polygalacturonases, or endoglucanases) (37,70), call into question any suggestion that B. thailandensis and, by extension, B. pseudomallei are typical plant pathogens. In fact, of the Ͼ30 described Burkholderia spp., only 6 are reported to cause plant disease (17,40), and none of these has a T3SS orthologous to T3SS2 bp .…”
Section: Discussionmentioning
confidence: 99%